2006
DOI: 10.1159/000091170
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of RANTES, CCR3 and CCR5 in the Lesional Skin of Patients with Atopic Eczema

Abstract: Background: Atopic eczema (AE) is a relapsing inflammatory disease based on IgE sensitization and characterized by peripheral blood eosinophilia and eosinophil infiltration into the lesional skin. In the patch test reaction of AE by allergens, an increased infiltration of activated eosinophils has been demonstrated peaking at 24–48 h. Regulated on activation normal T cell expressed and secreted (RANTES/CCL5) is a chemokine that induces eosinophil migration, and CCR3 and CCR5 are the receptors of RANTES. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…22,23 We found a substantially higher gene expression of CCL5/RANTES in AD in comparison with psoriasis and normal skin, which probably plays a major role in the orchestration and recruitment of eosinophils in ongoing inflammation in AD. [24][25][26] Our evaluation of DC subsets provides important new information that could help explain T-cell polarization in AD versus psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 We found a substantially higher gene expression of CCL5/RANTES in AD in comparison with psoriasis and normal skin, which probably plays a major role in the orchestration and recruitment of eosinophils in ongoing inflammation in AD. [24][25][26] Our evaluation of DC subsets provides important new information that could help explain T-cell polarization in AD versus psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that many cell types present in asthmatic airways, allergic rhinitis and atopic dermatitis have the capacity to generate CCL5/RANTES, which directly supported the potential role of CCL5/RANTES in these diseases 7,9,10,11,16 . Increased expression of CCL5/RANTES was observed in the lesional skin of patients with atopic eczema, and cDNA for CCL5 was upregulated in allergic rhinitis 16,17 . It was also demonstrated that the level of CCL5/RANTES in exhaled breath condensate was significantly correlated with parameters of airflow limitation 18 .…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the axes of chemokines and their receptors for T-cell trafficking are heterogeneous both within disease phenotypes and within patients in allergic diseases. [40] CCL2 MCP-1/MCAF/TDCF AA (BALF), AD (serum, PBMC) [70,89] CCL3 MIP-1α/LD78α AA (BALF), AD (PBMC) [70] CCL3CL1 LD78β CCL4 MIP-1β AD (serum, PBMC) [89] CCL5 RANTES AA (BALF), AD (skin biopsies, serum, PBMC) [70,79,88,89] CCL6 -CCL7 MCP-3 AA (BALF) [79] CCL8 MCP-2 CCL9 -CCL10 -…”
Section: T-cell Trafficking In Atopic Dermatitismentioning
confidence: 99%
“…In addition, the level of CCL11 in the lavage is significantly correlated with disease activity of allergic rhinitis [87]. In skin lesions of AD patients, CCL5, -11, -13 and -24 upregulation is associated with eosinophil accumulation [88][89][90]. Dermal fibroblasts, mononuclear cells and eosinophils are major sources of these chemokines [88][89][90].…”
Section: Eosinophil Trafficking In Allergic Rhinitis and Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation